The 7 habits of highly effective teens : A true gift for the teenage soul - Covey, Sean. (New York : Simon & Schuster paperbacks, 1998)
Applies the proven wisdom of the 7 habits to teens and the tough issues and life-changing decisions they face.
An abridged recording of the book read by the author.
In container (17 cm.).
Keywords: Teenagers -- Conduct of life; Success -- Psychological aspects; Teenagers -- Life skills guides; Audiobooks